The Gambia : Ex-Post Assessment of Longer-Term Program Engagement-an Update. (IMF Staff Country Reports; Country Report ;, 2011)
The performance of the Gambian economy has been strong in recent years. The authorities noted that in addition to providing financial resources, the program has helped to restore compliance with the rules on government borrowing from the Central Bank of The Gambia (CBG) following securitization arrangements between the government and the CBG, which allowed for CBG bridge financing in the absence of programmed EU budget support, and started TA in tax policy and administration, PFM, and liquidity forecasting. In the financial sector, progress has been made to preserve the solvency of banks.